1974
DOI: 10.1111/j.1537-2995.1974.tb04576.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Patterns of ABO Isoagglutinins in Normal Children Correlated with the Effects of Age, Sex, and Maternal Isoagglutinins

Abstract: The developmental patterns of ABO saline isoagglutinins were determined in 272 children between birth and 16 years of age. The frequency of saline isoagglutinins was significantly higher in group O‐O maternal‐cord pairs compared to group A‐O paired sera. The anti‐A and anti‐B titers increased gradually from 3 to 12 months: 30 per cent of group O and B children attained adult median titers of isoagglutinin, whereas only 4 per cent of group A children acquired adult anti‐B titers. This slow development of anti‐B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
6

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 13 publications
1
75
1
6
Order By: Relevance
“…The usual screening test for functional IgM antibodies is the measurement of isoagglutinins (42). However, since not all infants develop isoagglutinins (type AB), and anti-B isoagglutinins are present in only a small proportion of infants by 1 yr of age, we used an assay for detecting IgM opsonic activity for E. coli to study functional IgM antibody in our population of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The usual screening test for functional IgM antibodies is the measurement of isoagglutinins (42). However, since not all infants develop isoagglutinins (type AB), and anti-B isoagglutinins are present in only a small proportion of infants by 1 yr of age, we used an assay for detecting IgM opsonic activity for E. coli to study functional IgM antibody in our population of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…42 This includes development of isohemagglutinins or "natural" antibodies to nonself A/B blood group antigens, which remain low during the first months of life. 43,44 On a trial of ABO-incompatible heart transplantation in infants, there were no cases of hyperacute or acute humoral rejection, nor clinical problems attributable to blood group incompatibility under the standard immunosuppression without splenectomy. 41 Analysis of the peripheral blood B cells from patients who had received ABO-incompatible heart grafts in their infancy showed that these cells were simultaneously incapable of producing antibodies against donor type A or B blood group antigens, yet produced antibodies against nondonor polysaccharides.…”
Section: Elimination Of B Cells Responding To Group a Carbohydrates 4571mentioning
confidence: 99%
“…This is thought to be due to the immaturity of the neonatal immune system, as even anti-A and anti-B are not detectable during the first few months of life [1]. Due to the exceedingly low likelihood of alloimmunization, American Association of Blood Banks (AABB) Standards allows for neonates to be transfused for up to 4 months without any additional compatibility testing [23].…”
Section: Incidence Of Minor Rbc Antigen Alloimmunization In Various Cmentioning
confidence: 99%
“…However, it is their ability to induce alloimmune responses which typically draws the greatest attention from immunohematologists and transfusion medicine specialists. While antibodies to the ‘major' A and B antigens appear ‘naturally' in the serum after the first few months of life [1], antibodies to minor RBC antigens most frequently arise following a foreign exposure, usually as a result of transfusion, pregnancy, or transplantation. …”
Section: Introductionmentioning
confidence: 99%